Barriers and supports for uptake of human papillomavirus vaccination in Indigenous people globally: A systematic review - Shannon E. MacDonald; Lisa Kenzie; Angeline Letendre; Lea Bill; Melissa Shea-Budgell; Rita Henderson; Cheryl Barnabe; Juliet R. Guichon; Amy Colquhoun; Heather Ganshorn; Nancy Bedingfield; Paul D. Vandenboogaard; et al. (PLOS Global Public Health, 2023)
Despite the availability of effective and safe human papillomavirus (HPV) vaccines that reduce the incidence and impact of cervical cancer and other cancers, HPV vaccine coverage rates remain persistently low and the cervical cancer burden disproportionately high among Indigenous people globally. This study aimed to systematically identify, appraise, and summarize the literature on documented barriers and supports to HPV vaccination in Indigenous populations internationally. Forty-three studies were included and an inductive, qualitative, thematic synthesis was applied. We report on 10 barrier themes and 7 support themes to vaccine uptake, and provide a quantitative summary of metrics. Focusing on Indigenous perspectives reported in the literature, we propose recommendations on community-research collaboration, culturally safe intergenerational and gender-equitable community HPV vaccine education, as well as multi-level transparency to ensure informed consent is secured in the context of reciprocal relationships. Although the voices of key informant groups (e.g., HPV-vaccine eligible youth and community Elders) are underrepresented in the literature, the identification of barriers and supports to HPV vaccination in a global Indigenous context might help inform researchers and health policy makers who aim to improve HPV vaccine uptake in Indigenous populations.